2016
DOI: 10.1038/srep26192
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection results in metabolic alterations in the gut microbiota different from those induced by other diseases

Abstract: Imbalances in gut bacteria have been associated with multiple diseases. However, whether there are disease-specific changes in gut microbial metabolism remains unknown. Here, we demonstrate that human immunodeficiency virus (HIV) infection (n = 33) changes, at quantifiable levels, the metabolism of gut bacteria. These changes are different than those observed in patients with the auto-immune disease systemic lupus erythaematosus (n = 18), and Clostridium difficile-associated diarrhoea (n = 6). Using healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…The former was characterized by enrichment of genes involved in LPS biosynthesis, bacterial translocation and inflammation, with depletion of genes encoding factors contributing to amino acid metabolism and energy processes[49]. A recent study suggested that HIV-1 infection results in metabolic alterations associated with changes in gut microbiota that differ from those induced in other diseases[83]. This “disease-dependent” impact on gut microbial activity was most notably characterized by a bacterial community with a reduced ability to synthesize a set of specific amino acids whereas these same amino acids are metabolized by bacteria from patients with systemic lupus erythaematosus (SLE) or Clostridium difficile infection[83].…”
Section: Linking Alterations In Microbe-associated Metabolites To Hivmentioning
confidence: 99%
“…The former was characterized by enrichment of genes involved in LPS biosynthesis, bacterial translocation and inflammation, with depletion of genes encoding factors contributing to amino acid metabolism and energy processes[49]. A recent study suggested that HIV-1 infection results in metabolic alterations associated with changes in gut microbiota that differ from those induced in other diseases[83]. This “disease-dependent” impact on gut microbial activity was most notably characterized by a bacterial community with a reduced ability to synthesize a set of specific amino acids whereas these same amino acids are metabolized by bacteria from patients with systemic lupus erythaematosus (SLE) or Clostridium difficile infection[83].…”
Section: Linking Alterations In Microbe-associated Metabolites To Hivmentioning
confidence: 99%
“…Directly related to this, HIV-1 infected patients are likely to harbor enteropathogenic bacteria that can catabolize tryptophan into immunomodulatory kynourenine derivatives, known to correlate with disease progression and mucosal immune disruption [6]. Indeed, it has been recently reported that HIV-1 infection leads to a significant and distinct impact on the metabolism of the gut ecosystem compared with other diseases [7]. In the course of HIV-1 infection, the chronic immune activation—partially due to a dysfunction of the GALT—with consequent microbial translocation has been linked with an increased production of interferon (IFN) gamma and IDO activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this observation, researches that followed showed that the microbiota is depleted in genes belonging to main energetic processes (pyruvate metabolism, glycolysis and gluconeogenesis) and amino acid metabolism [63] which could impact on cART-mediated reconstitution of CD4+ T-cells [69]. In addition, bacterial genera enriched in HIV-infected, untreated subjects were found to encode enzymes involved in tryptophan catabolism [70,71], an independent predictor of non-AIDS comorbidities and death [52,72], thus entailing that the dysbiotic bacteria in HIV infection may directly contribute to immunoactive tryptophan catabolism in HIV and negatively impact on overall mortality [70].…”
Section: The Metabolic Pathways Of a Dysbiotic Microbiome May Drive Imentioning
confidence: 80%